Uso das ferramentas computacionais Scriptlattes, ScriptGP e Patent2net para an??lise da produ????o bibliogr??fica e tecnol??gica sobre a dengue - Nigro, Carolina Alencar (2016)
In Brazil, investments in Science and Technology have increased considerably, being considered an evolution in the field of scientific knowledge. Following this enrichment and in order to monitor the productivity of the researchers and research groups, CNPq (National Council for Scientific and Technological Development) has created a comprehensive curriculum base, called Lattes Platform, as well as a Directory of Research Groups in Brazil. Also, regarding the aspects of development and knowledge, patents are seen as a way to express the country???s technological and financial growth, and these documents are deposited in databases such as Espacenet. Such platforms, which are considered non-reference databases, allow information view, but do not provide direct access to massive extraction of such data, especially because they are allocated in a region of internet called deep web. This region cannot be accessed by common search engines, but by special data mining programs, known as crawlers. Thus, the aim of this research was to use computational tools Scriptlattes, ScriptGP and Patent2net, respectively, for: 1 ??? mining data regarding Brazilian research competencies in dengue; 2 - checking the evolution of Brazilian research groups on dengue; 3 ??? analyzing the progress of patents on dengue worldwide. These aims can enable a critical evaluation of the progress of academic and technological productivity on a neglected disease of particular relevance as dengue, being considered a major public health problem in Brazil and in other countries around the world. The results confirmed the effectiveness of the crawlers Scriptlattes, ScriptGP and Patent2net: 1 - in the compilation of performance indicators of the researchers, allowing the analysis of the progress of bibliographic, technical and technological productions on dengue; 2 - to identify the main poles of dengue research in the country, comparing the historical series of the disease with the history of creation of the research groups; 3 ??? in the identification of dengue patents deposited worldwide. In conclusion, the data of this work enabled an accurate analysis of the progress of dengue research in the country, in the field of health management. Furthermore, it has provided information that could be used to create or reformulate strategies concerning the planning of research related to the diagnosis, treatment and prevention of dengue.